STABILITY OF EMOTIONAL AND EMOTIONAL EXPERIENCES (Proceedings of International Educators Conference, 2023)
This article investigates the stability of emotional experiences over time, aiming to shed light on the factors influencing emotional stability and its implications for psychological well-being. The study employs a longitudinal approach, analyzing data gathered from a diverse sample to discern patterns and trends in emotional experiences. The findings contribute to our understanding of emotional resilience and provide valuable insights for interventions aimed at promoting mental health.